The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1038/s41598-019-38790-6
|View full text |Cite
|
Sign up to set email alerts
|

Safety of temporary ileostomy via specimen extraction site in rectal cancer patients who underwent laparoscopic low anterior resection

Abstract: If anastomotic site leakage is expected after laparoscopic low anterior resection (LAR), de-functioning ileostomy is required. However, there is controversy about the consequence of stoma formation via the specimen extraction site (SES). Therefore, we aimed to investigate stoma-related complication according to stoma formation via the SES. We enrolled rectal cancer patients who underwent laparoscopic LAR with temporary ileostomy between January 2013 and December 2017. Patients were divided into two groups: sto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 12 publications
1
12
0
Order By: Relevance
“…In this study, we found that the SSES group had smaller intraoperative blood loss, shorter operation time and shorter post-operative hospital stay than the SNS group before PSM, and the SSES group had shorter operation time after PSM. These results were similar with previous studies [13][14][15][16], the possible reason was that the SSES group omitted the step of suturing the incision, which greatly reduced the operation time.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…In this study, we found that the SSES group had smaller intraoperative blood loss, shorter operation time and shorter post-operative hospital stay than the SNS group before PSM, and the SSES group had shorter operation time after PSM. These results were similar with previous studies [13][14][15][16], the possible reason was that the SSES group omitted the step of suturing the incision, which greatly reduced the operation time.…”
Section: Discussionsupporting
confidence: 90%
“…We summarize the detailed viewpoints in Table 5 concerning the difference between SSES and SNS. Some studies reported that there was no statistically significant difference between the SSES group and SNS group in all stoma related complications [13,14,17]. However, Li W et al [15] reported the SSES had group had a lower parastomal hernia rate.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations